Data Privacy and Security in AI-Enabled Platforms: The Role of the Chief Infosec Officer - Gupta, Hari; Gupta, Vikhyat (Stallion Journal for Multidisciplinary Associated Research Studies, 2024)
In the age of digital transformation, artificial intelligence (AI)-enabled platforms have become central to a wide array of industries, driving innovation, efficiency, and personalization. However, the integration of AI technologies introduces significant challenges related to data privacy and security, as sensitive information is increasingly processed and analyzed by autonomous systems. The Chief Information Security Officer (CISO) plays a crucial role in navigating these challenges, ensuring that the privacy of user data is maintained while safeguarding against potential cyber threats. This paper explores the pivotal responsibilities of the CISO in AI-enabled platforms, focusing on the implementation of robust data protection frameworks, compliance with regulatory requirements, and the development of AI-specific security protocols. It also highlights the importance of fostering a culture of security within organizations, addressing the ethical implications of AI data usage, and managing the risks associated with AI-driven decision-making. By examining the evolving landscape of data privacy and security in AI, this work underscores the necessity of a proactive and strategic approach to safeguard both corporate and user interests in the digital age.